2015
DOI: 10.1039/c5gc00365b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient regioselective synthesis of pyrroles via a tandem enamine formation–Michael addition–cyclization sequence under catalyst- and solvent-free conditions

Abstract: An efficient three-component, catalyst-, solvent-, and column chromatography-free procedure was developed for the synthesis of 3-(1H-pyrrol-3-yl)indolin-2-ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…It also indicated that the catalyst is not required for the conjugate addition and annulation (eqs v and vi). 14 , 15 However, the presence of a catalyst is compulsory for the MS rearrangement of propargyl alcohol ( Table 1 , entry 8). On the basis of these observations, the mechanism for the one-pot synthesis of oxindolyl-pyrrole is presented in Scheme 6 .…”
Section: Resultsmentioning
confidence: 99%
“…It also indicated that the catalyst is not required for the conjugate addition and annulation (eqs v and vi). 14 , 15 However, the presence of a catalyst is compulsory for the MS rearrangement of propargyl alcohol ( Table 1 , entry 8). On the basis of these observations, the mechanism for the one-pot synthesis of oxindolyl-pyrrole is presented in Scheme 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Automation of the Hantzsch reaction was performed by Herath et al [53] with an approach to continuous flow chemistry [54]. The process takes place in a microreactor containing pyrrole-3carboxilic acids (17) and pyrrole-3-carboxilic highly substituted esters (18) with yields above 40%. The technique involves a 1 mL glass reactor with two injection points at which the preheated solutions of the reactants in DMF are introduced, the reactor temperature is maintained at 200°C, and the time in the reactor is no longer than 8 min (Scheme 16).…”
Section: Hantzsch Pyrrole Reactionmentioning
confidence: 99%
“…Another multicomponent reaction was developed by Vivekanand [17]; the procedure follows a catalyst-free methodology in which a number of green solvents, such as ethanol, water, PEG-200, glycerol and lactic acid, are tested for the sequential reaction that involves enamine formation, Michael addition and cyclization of primary amines, 1,3-dicarbonyl compounds and isatin-derived compounds that afforded 3-(1H-pyrrol-3-yl)indolin-2-ones (20) (Scheme 23). Using water, glycerol, PEG-200 and a solvent-free medium, they showed that the solvent-free conditions are better regardless of the nature of the starting materials.…”
Section: Other Multicomponent Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of syntheses of heterocycles from the early days are MCR, and these reaction sequences paved the way to a multitude of applications. Since last one decade, numerous efforts have been taken for development of these technique for synthesis of various organic …”
Section: Introductionmentioning
confidence: 99%